Funk’s physical and affective spaces: the local musicking of São Paulo’s lesbian parties - Martins, Raquel Mendonça (GIS - Gesture, Image and Sound - Anthropology Journal, 2021)
The article presents an analysis of ethnography carried out in the scene of lesbian parties that take place in Downtown São Paulo, where an eroticized funk circulates, as well as interviews with participants of the scene during the Covid_19 pandemic. The field comprehends two parties: “Sarrada no Brejo” and “Fancha”, (local funk brazilian parties). Based on the notion of local musicking, as well as locality, displacement and intersectionality I analyze the ways of how funk promotes an engagement among the participants, supporting the processes of transformation and identification that configure the lesbian, fat and black bodies. Observing funk music, the performance and the localities involved, I identify in this way of musicking a set of actions that resignify stereotypes and the body considered as an abject, transforming it into a political body through fun, occupation and creation of spaces.